Anything goes : a biography of the roaring twenties - Moore, Lucy, 1970- (New York : Overlook Press, 2010)
An exhilarating portrait of the era of jazz, glamour, and gangsters. The glitter of 1920s America was seductive, from flappers and wild all-night parties to the birth of Hollywood and a glamorous gangster-led crime scene flourishing under Prohibition. But the period was also punctuated by momentous events--the political show trials of Sacco and Vanzetti, the huge Ku Klux Klan march down Washington DC's Pennsylvania Avenue--and it produced a dizzying array of writers, musicians, and film stars, from F. Scott Fitzgerald to Bessie Smith and Charlie Chaplin. Historian Lucy Moore interweaves the stories of the compelling people and events that characterized the decade to produce a portrait of the Jazz Age, revealing an epoch of passion and change--an age, she observes, not unlike our own.--From publisher description.
"You cannot make your shimmy shake on tea" -- "The rhythm of life" -- Femme fatale -- "Five and ten cent lusts and dreams" -- "My God! How the money rolls in" -- "The business of America is business" -- Fear of the foreign -- The Ku Klux Klan redux -- In exile -- The New Yorker -- "Yes, we have no bananas today" -- The spirit of St. Louis -- The big fight -- Crash.
Includes bibliographical references and index.
Keywords: United States -- History -- 1919-1933.; United States -- Social life and customs -- 1918-1945.; United States -- History -- 1919-1933 -- Biography